2019
DOI: 10.2514/1.b37463
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and Vorticity Wave Generation in Realistic Gas Turbine Combustors

Abstract: Understanding the nature of the unsteady flow at the combustor exit is required to accurately simulate time dependent phenomena in the turbine entry, such as indirect noise generation. Using Large Eddy Simulations of the combustion process in a realistic geometry, we analyse the flow at its exit. Two realistic, near-ground certification operating conditions are considered. Different mechanisms for large-scale flow and thermal structure generation are described, which are ejected into the turbine. Modal decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…Sattelmayer [9] states that entropy waves are diffused by the flow turbulence, whereas in [10], the authors demonstrate that entropy wave dispersion from combustor to turbine is weak and the entropy wave strength is preserved at the combustor exit. Furthermore, Semlitsch et al [11] have demonstrated by means of a computational study that swirl also persists at the combustor exit.…”
Section: Introductionmentioning
confidence: 99%
“…Sattelmayer [9] states that entropy waves are diffused by the flow turbulence, whereas in [10], the authors demonstrate that entropy wave dispersion from combustor to turbine is weak and the entropy wave strength is preserved at the combustor exit. Furthermore, Semlitsch et al [11] have demonstrated by means of a computational study that swirl also persists at the combustor exit.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the intricate balance between heat release, turbulence and mixing in this configuration poses challenges for the numerical modeling and a more stable, V-shape configuration can be observed instead (Langella et al, 2020). The expected M-shape was predicted by Semlitsch et al (2019) for this configuration using model C of Table 1 with a dynamic evaluation of the combustion model constant; however, whether this shape was a result of an optimised value of the model constant (via dynamic evaluation) in the SDR model was not investigated. Additional simulations using the subgrid SDR models A and B of Table 1 are carried out in this study and observed to lead respectively to a too-weak M-flame and a strong V-flame near the pilot, regardless of the value used for the model constant within the range indicated in Table 1.…”
Section: Test Case: Bi-stable Combustor Of Aeronautical Interestmentioning
confidence: 99%
“…Entropy generation has been the subject of recent investigations using low-order models (Chen, Bomberg & Polifke 2016), numerical simulations (Semlitsch et al. 2019) and experimental measurements (Wang et al. 2019; Weilenmann et al.…”
Section: Introductionmentioning
confidence: 99%
“…Yoon (2020) found that the entropic cutoff frequency is inversely proportional to the flame residence time. Entropy generation has been the subject of recent investigations using low-order models (Chen, Bomberg & Polifke 2016), numerical simulations (Semlitsch et al 2019) and experimental measurements (Wang et al 2019;Weilenmann et al 2020a).…”
mentioning
confidence: 99%